(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
The problematic notion of the «aesthetic object» prevents us from understanding the real nature of the aesthetic dimension. Therefore, a survey of the aesthetic relation as a cognitive attitude should take the place of the ontology of the aesthetic object. Such a reversal of perspective has the merit of invalidating the essentialist strategy but may result in disregarding the objectual pole of the aesthetic relation and reducing the notion of aesthetic to a psychological purely internal and subjective process or to a symbolic-interpretative relation. How does an object with an economical, ritual, religious or instrumental purpose works when it gets into an aesthetic relation? Recently, socio-cultural and evolutionary anthropologists have proposed some interpretative categories like «agency» or «artification» that face the question with a praxeological rather than semantic approach.This paper aims to integrate these notions within a expressivist theory of the aesthetic behavior. Starting from a description of perception as an expressive activity and of the aesthetic attitude as a dynamical interplay between emotion and cognition, the purpose is to propose a theory of how an object works in an aesthetic mode, a theory that must be able to escape both pansemiotism and cognitivist and emotivist subjectivism.